PALEOCEANOGRAPHY AND CLIMATE OF THE BADENIAN (MIDDLE MIOCENE, 16.4-13.0 MA) IN THE CENTRAL PARATETHYS BASED ON FORAMINIFERA AND STABLE ISOTOPE (δ18O AND δ13C) EVIDENCE - Báldi K. (My University, 2006)
Benthic foraminifera and stable isotopes analyses revealed changes emerging in the paleoceanographic scenery in the Paratethys. The percentage of inbenthic, oxyphylic taxa and diversity in the benthic foraminiferal assemblage showed increasing food supply (organic matter), decreasing oxygen level and growing stress on the sea floor. Oxygen isotopes measured in planktonic and benthic foraminifera pointed to strengthening stratification during the Badenian period. The carbon isotopes indicated intensified accumulation of light marine organic matter. This increasing stratification trend is especially pronounced by Late Badenian (13.5-13 Ma) when surface water oxygen isotope values are rather negative. A simple two-layer circulation model was worked out for the Badenian Paratethys explaining these characteristic environmental changes. An antiestuarine (lagoonal) circulation is assumed for the Central Paratethys during the Early (16.4-15 Ma) and mid Badenian (15-13.5 Ma). The mid Badenian period of time comprises the short episode of evaporite formation in the Carpathian Foredeep and the Transylvanian Basin. Evidence presented here supported a reversal of circulation to estuarine type after the deposition of salts by Late Badenian (13.5-13 Ma). The Early Badenian antiestuarine circulation is suggested to associate with the high temperatures of the Mid-Miocene Climatic Optimum, and the Late Badenian estuarine circulation with the cooler period following it. © Springer-Verlag 2005.
Keywords: CLIMATE; FORAMINIFERA; MIOCENE; PARATETHYS; STABLE ISOTOPES; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен